Belvosia sp. (Diptera: Tachinidae) parasitizing halysidota sp. (Lepidoptera: Arctiidae) caterpillars on ficus benjamina (Moraceae) in Brazil - De Souza Tavares, Wagner; Nunez, Enio; Serrão, José Eduardo; Soares, Marcus Alvarenga; Wilcken, Carlos Frederico [UNESP]; Zanuncio, José Cola (My University, 2014)
Ficus benjamina L. (Moraceae) is an exotic ornamental plant in Brazil. The aim of this study was to identify a defoliator and its parasitoid on F. benjamina plants in Viçosa, Minas Gerais, Brazil and to determine the number of pupae and the emergence of lepidopteran and a dipteran. Four Halysidota sp. (Lepidoptera: Arctiidae) groups, with 158, 144, 137 and 129 last-instar caterpillars aggregated on the trunks of 4 F. benjamina trees. These caterpillars were collected, held in plastic containers with ficus leaves until development and emergence were completed. Adults of 1 undescribed lepidopteran species (Halysidota) and 1 dipteran species [Belvosia (Tachinidae)] emerged from the Halysidota pupae. An average of 118 viable Halysidota pupae per group were formed, and an average of 62.5 Belvosia individuals emerged from these host pupae per Halysidota group. From a grand total of 472 Halysidota pupae only one adult emerged. Halysidota sp. damaged F. benjamina plants in Viçosa, Minas Gerais, Brazil, but this defoliator was parasitized by Belvosia sp. The findings reported here indicate that Belvosia sp. appears to have the potential to reduce populations of Halysidota sp. and possibly protect F. benjamina in ornamental plantings.
Keywords: Arctiinae; Exoristinae; Gregarism; Parasitism; Rosales